The Effectiveness of Progressive Muscle Relaxation on Reducing Depression Levels in the Elderly in Workplaces Muslim Elderly Home - Adhijaya Pendit, Saka; Dayuningsih; Dwi febriana, Anissa (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Depression can arise due to increased stress factors and reduced adaptability in older adults. Its effects include decreased appetite, weight loss, digestive problems, and sleep disorders. On the other hand, the psychological effects that can be caused by depression include the risk of suicide. Progressive muscle relaxation therapy is carried out in stages. This helps reduce muscle tension caused by depression, so that the body becomes relaxed and the mind calm. ROP therapy activates the parasympathetic nervous system and regulates the hypothalamus to reduce stress signals, thereby reducing stress levels in the elderly, especially those experiencing depression. The purpose of this study was to analyze the effectiveness of progressive muscle relaxation in reducing depression levels in elderly people in the Muslim Nursing Home Work Area. Method: The research design was quasi-experimental, using a pre-post test single group design with a sample size of 15 respondents and purposive sampling according to the inclusion criteria. Depression levels were measured using the Geriatric Depression Scale (GDS) instrument. The data were analyzed using the Wilcoxon test. Result: The results showed that progressive muscle relaxation therapy was effective in reducing depression levels in the elderly with a p-value (0.002) < p-value (0.05). This means that progressive muscle relaxation therapy is effective in reducing depression levels in the elderly in the Muslim Nursing Home Work Area. Conclusion: Based on the results of the study, progressive muscle relaxation therapy is more effective in helping to reduce depression levels in the elderly. Progressive muscle relaxation therapy is beneficial for reducing depression in the elderly and is recommended as a non-pharmacological nursing therapy.